Reinterpretation of traumatic experience: the concept of post-traumatic growth - SIROKHA, Liliia; PROKOPOVICH, Evgeniy; RYABCHICH, Yaroslav (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
This article presents a detailed analysis of the concept of post-traumatic growth, defined as the positive psychological changes that may arise from facing and adapting to traumatic events. The authors explore both historical and contemporary perspectives on understanding the effects of trauma on individual development. Considering ongoing societal challenges – including natural disasters, social upheavals, military conflicts, and personal crises – the investigation into the potential for post-traumatic growth is especially relevant. Despite the difficulties associated with trauma, research has identified opportunities for personal empowerment, shifts in life values, and improvements in interpersonal relationships for those who have faced trauma. The article underscores that post-traumatic growth not only encourages a reevaluation of conventional perceptions regarding the psychological aftermath of trauma but also opens pathways for personal transformation and enhanced overall well-being. The concept of post-traumatic growth emphasizes the possibility of positive adaptation and transformation in response to extreme life challenges. Special attention is given to the importance of social support, optimism, and personal qualities in achieving post-traumatic growth. However, it is essential to recognize that post-traumatic growth is not an automatic outcome of trauma; instead, ongoing personal distress and growth frequently coexist. In the context of this process, the authors examine the dynamics of post-traumatic adaptation, which includes active adjustment to altered life conditions and cognitive reinterpretation of experienced events. This can lead to personal strengthening, a deeper understanding of life values, and enhanced interpersonal relationships. The concepts of post-traumatic growth hold significant potential for psychology and psychotherapy, as they facilitate the development of effective strategies for supporting and rehabilitating individuals who have experienced traumatic events. A deeper understanding of the processes of growth following trauma contributes to the development of individualized approaches to strengthening internal resources, enhancing resilience, and improving overall psychological well-being.